The Influence Of The Level Of Taxpayer Compliance On Motor Vehicle Tax Revenue In The Regional Revenue Agency Of North Sulawesi Province Year 2019-2021 - DEWI, Ade Ayu Prita; KALANGI, Lintje; WALANDOUW, Stanley Kho (PT Keberlanjutan Strategis Indonesia, 2022)
Taxes are mandatory contributions to the state owed by individuals or entities that are coercive in nature and can be enforced by law, by not receiving direct compensation and being used for the needs of the state for the greatest prosperity of the people. This study aims to determine the effect of the level of taxpayer compliance on motor vehicle tax revenue at the Regional Revenue Agency of North Sulawesi Province. Dengan tujuan untuk mengetahui pengaruh signifikan tingkat kepatuhan wajib pajak terhadap penerimaan pajak kendaraan bermotor. Jenis data penelitian yang digunakan penelitian ini menggunakan pendekatan kuantitatif. Penelitian ini menggunakan metode asosiatif yaitu penelitian yang mencari pengaruh antar variabel independen (X) terhadap variabel dependen (Y). This study aims to examine and explain the effect of the level of taxpayer compliance on motor vehicle tax revenue. The population in this study is the level of taxpayer compliance and data on the realization of motorized vehicle tax revenue from 15 Samsat in North Sulawesi Province for the 2019-2021 period. The sample is part of the number and characteristics possessed by the population. This study uses a saturated sample where all populations are used as samples. The data analysis technique used in this study is simple linear regression. The results of this study are that the variable Taxpayer Compliance Level has a significant effect on Motor Vehicle Tax Receipts at the Regional Revenue Agency of North Sulawesi province.